2021
DOI: 10.3390/ijms22052339
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Changes Associated with Loss of Cell Viability Induced by Oxysterol Treatment of a Retinal Photoreceptor-Derived Cell Line: An In Vitro Model of Smith–Lemli–Opitz Syndrome

Abstract: Smith–Lemli–Opitz Syndrome (SLOS) results from mutations in the gene encoding the enzyme DHCR7, which catalyzes conversion of 7-dehydrocholesterol (7DHC) to cholesterol (CHOL). Rats treated with a DHCR7 inhibitor serve as a SLOS animal model, and exhibit progressive photoreceptor-specific cell death, with accumulation of 7DHC and oxidized sterols. To understand the basis of this cell type specificity, we performed transcriptomic analyses on a photoreceptor-derived cell line (661W), treating cells with two 7DHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 259 publications
0
1
0
Order By: Relevance
“…Oxysterols are cholesterol derivatives produced via enzymatic or free radical oxidation associated with oxidative stress, inflammation, and apoptosis ( Testa et al, 2018 ; Zarrouk et al, 2020 ; de Medina et al, 2022 ). Several studies have suggested a correlation between retinal degeneration and cholesterol metabolism, specifically the transformation of cholesterol into oxysterols and the degeneration of the retina ( Pfeffer et al, 2021 ; Zhang et al, 2021 ). Dasari et al (2011) observed that providing rabbits with a diet high in cholesterol for 12 weeks resulted in heightened β-amyloid (Aβ) levels in the retina, oxidative harm, apoptosis, and elevated accumulation of cholesterol and oxysterols (24-hydroxycholesterol (24-OH), 27-hydroxycholesterol (27-OH), 4β-hydroxycholesterol, 7α-hydroxycholesterol, 25-hydroxycholesterol (25-OH), 7-ketocholesterol (7KC), and 7β-hydroxycholesterol (7β-OH)).…”
Section: Gm Composition and Metabolites Influence Amd Developmentmentioning
confidence: 99%
“…Oxysterols are cholesterol derivatives produced via enzymatic or free radical oxidation associated with oxidative stress, inflammation, and apoptosis ( Testa et al, 2018 ; Zarrouk et al, 2020 ; de Medina et al, 2022 ). Several studies have suggested a correlation between retinal degeneration and cholesterol metabolism, specifically the transformation of cholesterol into oxysterols and the degeneration of the retina ( Pfeffer et al, 2021 ; Zhang et al, 2021 ). Dasari et al (2011) observed that providing rabbits with a diet high in cholesterol for 12 weeks resulted in heightened β-amyloid (Aβ) levels in the retina, oxidative harm, apoptosis, and elevated accumulation of cholesterol and oxysterols (24-hydroxycholesterol (24-OH), 27-hydroxycholesterol (27-OH), 4β-hydroxycholesterol, 7α-hydroxycholesterol, 25-hydroxycholesterol (25-OH), 7-ketocholesterol (7KC), and 7β-hydroxycholesterol (7β-OH)).…”
Section: Gm Composition and Metabolites Influence Amd Developmentmentioning
confidence: 99%